2021
DOI: 10.3390/ma14133694
|View full text |Cite
|
Sign up to set email alerts
|

Additively Manufactured Zirconia for Dental Applications

Abstract: We aimed to assess the crystallography, microstructure and flexural strength of zirconia-based ceramics made by stereolithography (SLA). Two additively manufactured 3 mol% yttria-stabilized tetragonal zirconia polycrystals (3Y-TZP: LithaCon 3Y 230, Lithoz; 3D Mix zirconia, 3DCeram Sinto) and one alumina-toughened zirconia (ATZ: 3D Mix ATZ, 3DCeram Sinto) were compared to subtractively manufactured 3Y-TZP (control: LAVA Plus, 3M Oral Care). Crystallographic analysis was conducted by X-ray diffraction. Top surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…According to the XRD analysis, the present study demonstrated that all zirconia groups (SM and AM) had comparable phase composition and pattern with tetragonal phase forming the bulk of the material, similar to what was reported by Nakai et al [ 29 ]. However, in our study, monoclinic phase was detected more apparently in the tilted group.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…According to the XRD analysis, the present study demonstrated that all zirconia groups (SM and AM) had comparable phase composition and pattern with tetragonal phase forming the bulk of the material, similar to what was reported by Nakai et al [ 29 ]. However, in our study, monoclinic phase was detected more apparently in the tilted group.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the effect size detected between AM and SM zirconia [ 29 , 32 ] and that between horizontally and vertically printed zirconia specimens [ 36 ], with a level of significance set at 0.05 and a power of 95%, each test group must contain 12 specimens ( , accessed on 7 September 2021). However, the number of specimens dedicated for BFS was increased to 15 to allow for Weibull analysis later as recommended by ISO standard #6872 [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although none of the groups examined were able to fully mimic the specimens’ virtual design, the AM zirconia with a porosity of 40% had the highest fabricating accuracy and the smallest volume change after manufacturing, followed by the 20% porosity and 0% porosity groups. Nakai et al [ 38 ] evaluated the crystallography, microstructure and flexural strength square-shaped SLA additively manufactured zirconia-based ceramics and compared with milled zirconia. AM 3Y-TZP; LithaCon 3Y 230 (Lithoz) with printing orientation 90-degree and 3D Mix zirconia (3DCeram Sinto) with 0-degree printing orientation and one alumina-toughened zirconia (ATZ) with 0-degree were compared with milled 3Y-TZP zirconia.…”
Section: Additive Manufacturing Techniques For Zirconia Ceramicmentioning
confidence: 99%
“…To date, X-ray analysis, optical, and scanning electron microscopy are the three most popular techniques applied by industrial and research practitioners to analyse microstructures [46][47][48]. In Mg alloys, the grain size in microstructures greatly influences mechanical and other tribological properties [27,33].…”
Section: Introductionmentioning
confidence: 99%